(untitled) (Journal of Engineering, 2003)
he present study has been carried out to investigate the effect of Elasto Hydrodynamic Lubrication (EHL) on the pressure distribution of cold rolling strip by taking new conditions, which give new results in the theoretical analysis. This analysis takes into consideration the variation of the yield stress of the material, the position of the neutral angle (0) and the shear stress along the direction of rolling.The results obtained from the numerical method are in good agreement with the previous experimental result.